Tendinous Tissue Adaptation to Explosive- vs. Sustained-Contraction Strength Training - Massey, Garry J.; Balshaw, Thomas G.; Maden-Wilkinson, Thomas M.; Tillin, Neale A.; Folland, Jonathan P. (Frontiers in Physiology, 2018)
The effect of different strength training regimes, and in particular training utilizing brief explosive contractions, on tendinous tissue properties is poorly understood. This study compared the efficacy of 12 weeks of knee extensor explosive-contraction (ECT; n = 14) vs. sustained-contraction (SCT; n = 15) strength training vs. a non-training control (n = 13) to induce changes in patellar tendon and knee extensor tendon-aponeurosis stiffness and size (patellar tendon, vastus-lateralis aponeurosis, quadriceps femoris muscle) in healthy young men. Training involved 40 isometric knee extension contractions (3 times/week): gradually increasing to 75% of maximum voluntary torque (MVT) before holding for 3 s (SCT), or briefly contracting as fast as possible to ~80% maximum voluntary torque (ECT). Changes in patellar tendon stiffness and Young’s modulus, tendon-aponeurosis complex stiffness, as well as quadriceps femoris muscle volume, vastus-lateralis aponeurosis area and patellar tendon cross-sectional area were quantified with ultrasonography, dynamometry, and magnetic resonance imaging. ECT and SCT similarly increased patellar tendon stiffness (20% vs. 16%, both p < 0.05 vs. control) and Young’s modulus (22% vs. 16%, both p < 0.05 vs. control). Tendon-aponeurosis complex high-force stiffness increased only after SCT (21%; p <0.02), while ECT resulted in greater overall elongation of the tendon-aponeurosis complex. Quadriceps muscle volume only increased after sustained-contraction training (8%; p = 0.001), with unclear effects of strength training on aponeurosis area. The changes in patellar tendon cross-sectional area after strength training were not appreciably different to control. Our results suggest brief high force muscle contractions can induce increased free tendon stiffness, though SCT is needed to increase tendon-aponeurosis complex stiffness and muscle hypertrophy.